Assessment of Cytotoxicity and Genotoxicity Potential of Effluents from Bahir Dar Tannery Using Allium cepa - Tayachew Admas; Bizuayehu Kerisew (Advances in Public Health)
Tannery effluent plays a significant role in increasing pollution in the environment; in particular, it contains toxic heavy metals which cause toxic effects on plant genetic materials. Among tannery effluent chemicals, chromium and lead have cytotoxicity and genotoxicity potentials on Allium cepa. This investigation was undertaken to assess the physicochemical properties of tannery wastewater and their effect on the genetic materials of A. cepa. Effluent’s physicochemical characteristics were investigated using digital instruments for direct measurement and standard methods of atomic absorption spectrophotometer colorimetric analysis. A series of six onion bulbs were grown in 0%, 20%, 40%, 60%, 80%, and 100% concentrations of wastewater (v/v) ratio, and root tips from each onion bulb were cut and processed for analysis by aceto-orcein squash technique. Most of effluent components were above the discharge limit standards set by Federal Environmental Protection Agency and Ethiopian Environmental Protection Authority. The cytotoxicity effect on the root growth showed a significant reduction at high concentration. Simple regression analysis showed that the results of mitotic index were statistically significant (P < 0.05) in different concentrations. A decrease in mitotic index with increasing concentration of the effluent was observed. The effluent had induced chromosomal abnormalities such as laggard, fragmentation, stickiness, bridge, micronucleus, and binucleated and morphologically changed nuclei in A. cepa root cells among others. The results showed that cytotoxicity, genotoxicity, and chromosomal aberrations were induced by the tannery effluent. Industries shall think of biological waste treatment methods.